Identification Of Barriers To Effective Treatment And Prevention Of Malaria In Khartoum, Sudan - Elhag, Elkhanssa Abdelhameed Ahmed (2019)
Malaria is one of the main causes of death in Sudan. The highest prevalence is among children and pregnant women. The estimated deaths were 3500 cases per year. Near thirteen percent of the hospital admissions were due to malaria. Despite the achievements of the National Malaria Control Programme in Sudan, still the targets on eradication and elimination were not reached. The current research was carried to identify the barriers to effective prevention and treatment of malaria in Sudan. The research was conducted in Khartoum state. A prospective cross-sectional survey was carried to assess the community pharmacist’s practices of malaria prevention and treatment. The public in Khartoum were also assessed for their malaria knowledge in addition to their prevention and treatment practices. Malaria treatment in a public hospital was also investigated retrospectively and prospectively. The results showed that community pharmacists had inadequate malaria knowledge and malaria treatment practices. About 66.2% of the surveyed community pharmacists had less than 50% knowledge score. There was significant relationship between pharmacist knowledge score and receiving training on malaria prevention and treatment (P-value 0.008). The research revealed under reporting of antimalarial adverse drug reactions (ADRs) by the community pharmacists. The community pharmacists reported lack of knowledge, lack of training and time as main barriers to their effective contribution in malaria prevention and treatment and ADRs reporting activities. The publics in Khartoum showed good knowledge regarding malaria symptoms, complications and drugs. About 86.9% mentioned mosquitos’ bites as the main cause of malaria.